(untitled) (Mediscope, 2022)
Objective: This cross-sectional study was carried out among the students of Rev. Paul’s High School, Gallamari, Khulna to assess the adolescents’ sedentary lifestyle and also the related factors. Methods: The sample size was 217 which were selected by systematic sampling method. Data were collected using a semi-structured questionnaire by a face-to-face interview conducted by the interviewer. Results: In this study, it was found that only 43.3% of respondents had sedentary habits (watching TV, internet browsing, playing video games and not liking to go outside for playing in the field). Comparatively majority of girls (57.8%) were associated with sedentary habits. Otherwise whose mothers are educated were not associated with sedentary habits (62.9%). In this study, it was observed that among those who like fast foods, the majority had sedentary habits (24.5%). Also, about 64.3% of respondents who have sedentary habits were unwilling to perform outdoor physical activities like playing. Conclusion: The findings of the result might help develop awareness among adolescents as well as parents and teachers regarding the sedentary lifestyle to reduce the risk of adverse health outcomes as well as to know about the associated factors. Thus, it will be helpful to minimize the factors from the daily lifestyle and become healthy citizens. Mediscope 2022;9(2): 68-74